The evolution of spirituality and the moral beginning in the ancient Turkic’s worldview - Aтaш, Б. М; Құрaнбек, Ә. A.; Тәттібек, Н. М. (Journal of Oriental Studies, 2017)
The article discusses the evolution of spirituality and moral principles of the ancient turkic worldview. First of all, reveals the specific difficulties and contradictions of the study of this problem, including: insufficient volume of materials written sources, preserved ancient manuscripts; specific understanding of spirituality, level of spirituality and wisdom in some moments become metaphysical in nature; still preserved in our minds europocentrism stereotypes; coverage of extended period of the age of prototurk. Next, the authors present an overview of spiritual and moral foundations of ancient religious faith, reveal and show the basic laws and the sources of the ethical teachings of the beginning of Zoroastrianism, the opposite two spirits, rituals with fire, the holiday «Nauryz», etc. features of spirituality. Further, taking into account the important role in tengriism such category as will and freedom, responsibility and duty, heroism and bravery reveals the moral-regulatory function of faith.